Volume based feeding versus rate based feeding in the critically ill: A UK study. (November 2019) - Bharal, Mina; Morgan, Sally; Husain, Tariq; Hilari, Katerina; Morawiec, Charlie; Harrison, Kirsty; Bassett, Paul; Culkin, Alison
Background: Underfeeding in intensive care patients on enteral nutrition is commonplace and multifactorial. This can be exacerbated by interruptions caused by routine fasting for procedures and investigations. Our study aims to demonstrate that a volume based feeding protocol can overcome the barriers of underfeeding and safely increase energy and protein delivery in UK intensive care patients, potentially improving clinical outcomes. Methods: In this single centre cohort study, data were collected from adult mechanically ventilated patients. We compared the standard care of rate based feeding, from an International Nutrition Survey (2014/15) to the new intervention of volume based feeding, in a mixed medical and surgical intensive care unit. The primary outcomes were the proportion of energy and protein daily targets delivered. Secondary outcomes compared the effects on gastrointestinal tolerance, glycaemic control, mortality, mechanical ventilation days, length of stay in intensive care unit and hospital. Results: From a total of 82 patients (rate based feeding = 27, volume based feeding = 55), volume based feeding patients received significantly more prescribed energy (52% versus 81%; p < 0.001) and protein (40% versus 74%; p < 0.001). There was no significant difference in gastrointestinal symptoms such as gastric residual volumes (p = 0.62), glycaemic control (p = 0.94) or insulin usage (p = 0.75). Although there was an improvement in energy and protein delivery, there were no differences in mechanical ventilation days (p = 0.12), mortality (p = 0.06), length of stay in intensive care unit (p = 0.93) and hospital (p = 0.72) between the groups. Conclusion: Compared to rate based feeding, volume based feeding significantly improved energy and protein provision with no adverse effects on glycaemic control or gastrointestinal tolerance, clinical outcomes were not affected.